Community Tolerance, Habitus, and Early Childhood Education in Schools: A Phenomenological Approach - Qadafi, Muammar; Alfan Sidik, Muhammad; Mukhtar, Zulfadhly (Al-Athfal: Jurnal Pendidikan Anak, 2024)
Purpose – This study examines how the tolerant culture of the Senggarang community, rooted in its traditions and values, influences religious tolerance education in early primary education in Tanjungpinang City, Indonesia, by utilizing Bourdieu’s theory of habitus and cultural capital to clarify the impact of cultural practices in multicultural communities on early childhood education oriented towards tolerance. Design/methods/approach – This study employs a qualitative phenomenological approach, utilizing direct observation, in-depth interviews, and document analysis to explore the influence of cultural practices on tolerance education. Field research engaged diverse informants from Senggarang, including elementary school teachers from early elementary education, local community members, and officials familiar with the area's historical and social dynamics, to ensure a comprehensive understanding of the community's tolerance-related practices. Findings – The findings reveal that the tolerant cultural practices in Senggarang, deeply rooted in historical and social contexts, significantly influence tolerance education among students. Children aged 6–7 years in early primary education adopt tolerance as part of the behaviors they learn through communal activities such as interfaith holiday celebrations and support for religious events. Cultural values that promote interfaith respect, evident in traditional interactions and mutual cooperation (gotong royong), are internalized by children through family and community engagement. These practices align with Pierre Bourdieu's concepts of habitus and cultural capital, demonstrating how inherited cultural norms and daily practices shape children's dispositions toward tolerance. Educators and the school environment further reinforce these practices by embedding tolerance education through routines and collaborative activities among diverse students. Research implications/limitations – This study provides valuable insights into how community culture influences school-based tolerance education. However, its findings may be less applicable to areas with different social and historical contexts. Future research could further examine the role of cultural capital and habitus in multicultural education contexts across various regions in Indonesia. Practical implications – The study highlights the importance of incorporating local cultural values into education to foster early tolerance, offering a model for using cultural practices as teaching tools in diverse communities. Originality/value – This study highlights how community culture and Bourdieu’s concepts of habitus and cultural capital enrich our understanding of tolerance education in first-grade primary school students (ages 6–7), encouraging further exploration of local cultural values to shape inclusive educational practices in multicultural societies. Paper type Research paper